Analisis Pengaruh Brand Equity untuk Meningkatkan Minat Beli Ulang dan Word Of Mouth (Studi Kasus Batik Gonggong Tanjungpinang) - Iranita Iranita (Bahtera Inovasi, 2019)
This study aims to analyze the effect of Brand Equity on increasing repurchase interest and Word of Mouth (WOM). The population and sample in this study were consumers who had already bought Tanjungpinang’s barking batik, both those in the city of Tanjungpinang, as well as consumers outside Tanjungpinang, especially those who had bought batik barking.Determination of the sample in this study using the method of Accidental Sampling is a sampling technique based on chance meeting with a number of criteria that are tailored to the purpose of the study so that selected 60 respondents who have met the criteria and are involved in this study by filling out the questionnaire that has been distributed. The data analysis technique used in this research is the Path Analysis method. The results of this study indicate that Brand Equity (Brand Awareness and Brand Image) has proven to have an effect on repurchase interest and Word of Mouth and these results prove that Brand Equity (Brand Awareness and Brand Image) have a role in bridging the influence that occurs on the variable repurchase interest and Word of Mouth. The results of this study can be a reference for the Tanjungpinang area to make Tanjungpinang as a citybranding of batik barking